PERAN STRATEGI PEMASARAN DALAM MENCIPTAKAN KEPUASAN PELANGGAN MELALUI MINAT BELI SEBAGAI VARIABEL INTERVENING PADA PRODUK PESTISIDA DHARMABAS 500 EC - Danur Febri Kurniawan; Thamrin Abdullah; Jubery Marwan (Bajang Institute, 2025)
The application of pesticides plays a crucial role in enhancing agricultural productivity, with Dharmabas 500 EC, a carbamate insecticide produced by PT Perusahaan Perdagangan Indonesia (PPI), being effective in controlling pests on rice, chili, onion, and sugarcane crops. Despite being available in the market for over three decades, the product faces significant competition, shifting consumer preferences, and fluctuating sales. This study aims to examine the impact of marketing strategies on purchase intention and customer satisfaction, employing a quantitative approach using Structural Equation Modeling with Partial Least Squares (SEM-PLS) techniques, based on data from 88 respondents. The findings reveal that marketing strategies have a significant effect on both purchase intention (path coefficient = 0.677) and customer satisfaction (path coefficient = 0.324), with purchase intention exerting a strong influence on customer satisfaction (path coefficient = 0.734). Furthermore, marketing strategies indirectly affect customer satisfaction through purchase intention (path coefficient = 0.497). These results suggest that well-executed marketing strategies, such as enhancing brand awareness, offering compelling promotions, and ensuring effective communication, can boost both purchase intention and customer satisfaction. To remain competitive in the pesticide market, PT PPI management should focus on strengthening data-driven marketing approaches, expanding digital promotions, and ensuring that their products meet or exceed consumer expectations.